Full stereochemical determination of ajudazols A and B by bioinformatics gene cluster analysis and total synthesis of ajudazol B by an asymmetric ortholithiation strategy - Essig, Sebastian; Bretzke, Sebastian (Journal of the American Chemical Society, 2012)
The stereochemical determination of the potent respiratory chain inhibitors ajudazols A and B and the total synthesis of ajudazol B are reported. Configurational assignment was exclusively based on biosynthetic gene cluster analysis of both ketoreductase domains for hydroxyl-bearing stereocenters and one of the first predictive enoylreductase alignments for methyl-bearing stereocenters. The expedient total synthesis resulting in unambiguous proof of the predicted stereochemistry involves a short stereoselective approach to the challenging isochromanone stereotriad by an innovative asymmetric ortholithiation strategy, a modular oxazole formation, and a late-stage Z,Z-selective Suzuki coupling.